Single-shot production of Janus graphene thin film for solar steam generation with 94.5% efficiency. (31st October 2022) - Yang, Tieshan; Lin, Han; Lin, Keng-Te; Mesa Saldarriaga, David; Yang, Guoliang; Guo, Chunsheng; Zhang, Huihui; Zhang, Jie; Fraser, Scott; Lau, Alan Kin-Tak; Ma, Tianyi; Jia, Baohua
Abstract: Interfacial solar-driven steam generation as a cost-effective green technology has shown a great potential in realizing water desalination and purification. To achieve high solar steam generation efficiency, it is important to simultaneously realize high solar absorption and effective water transportation. Among various solar absorbers, Janus structures composed of different layered materials for multiple functions have been demonstrated to be promising for high efficiency. However, the complex material composition and the corresponding multistep fabrication process become a barrier for high efficiency realization and large-scale applications. Developing a simple, low-cost, and fast fabrication process holds the key to producing Janus absorbers with high efficiency. Herein, we propose and demonstrate a monolithic Janus absorber fabricated by a single shot flash reduction of an ultrathin (370 nm) graphene oxide film within a millisecond time frame. By synchronising the advantages of a top three-dimensional (3D) porous graphene structure for high solar absorption (99%) and a bottom two-dimensional (2D) layered graphene oxide structure for efficient water transportation, the fabricated Janus absorber achieves high solar-to-vapour conversion efficiency of 94.5% under one sun illumination and steady water production (2.054 kg m −2  h −1 ). Such a large-scale high yield production method is orders of magnitude faster than the state-of-the-art Janus film fabrication method and offers a highly efficient and reliable approach for solar water desalination and purification. Graphical abstract: Image 1